Cysteine protects rabbit spermatozoa against reactive oxygen species-induced damages. - Zhendong Zhu; Zhanjun Ren; Xiaoteng Fan; Yang Pan; Shan Lv; Chuanying Pan; Anmin Lei; Wenxian Zeng (PLoS ONE, 2017)
The process of cryopreservation results in over-production of reactive oxygen species, which is extremely detrimental to spermatozoa. The aim of this study was to investigate whether addition of cysteine to freezing extender would facilitate the cryosurvival of rabbit spermatozoa, and if so, how cysteine protects spermatozoa from cryodamages. Freshly ejaculated semen was diluted with Tris-citrate-glucose extender supplemented with different concentrations of cysteine. The motility, intact acrosomes, membrane integrity, mitochondrial potentials, 8-hydroxyguanosine level and sperm-zona pellucida binding capacity were examined. Furthermore, glutathione peroxidase (GPx) activity, glutathione content (GSH), and level of reactive oxygen species (ROS) and hydrogen peroxide of spermatozoa were analyzed. The values of motility, intact acrosomes, membrane integrity, mitochondrial potentials and sperm-zona pellucida binding capacity of the frozen-thawed spermatozoa in the treatment of cysteine were significantly higher than those of the control. Addition of cysteine to extenders improved the GPx activity and GSH content of spermatozoa, while lowered the ROS, DNA oxidative alterations and lipid peroxidation level, which makes spermatozoa avoid ROS to attack DNA, the plasma membrane and mitochondria. In conclusion, cysteine protects spermatozoa against ROS-induced damages during cryopreservation and post-thaw incubation. Addition of cysteine is recommended to facilitate the improvement of semen preservation for the rabbit breeding industry.